Analisis Tindak Pidana Kejahatan Siber “Studi Kasus Penipuan Tiket Konser NCT Dream the Dream Show 2” - Karunia; Muhammad Fauzan Al Fikri; Lilik Prihatini (DOKTRINA: JOURNAL OF LAW, 2024)
Cybercrime can be defined as "An offense committed against a person or group of people with criminal motives to intentionally damage the victim's reputation or cause physical or mental harm or loss to the victim". The Indonesian government has passed a cybercrime law known as ITE Law Number 11 of 2008 which has been amended to Law Number 19 of 2016. NCT Dream is the third sub-unit of the South Korean boy band, NCT which was founded by SM Entertainment in 2016.The research method used by the author is a qualitative research method. The South Korean boy band, NCT Dream held a concert entitled The Dream Show 2 in Jakarta which was held on March 4, 5 and 6, 2023 at the Indonesia Convention Exhibition (ICE) BSD. However, at the time of ticket sales, there were many fraudulent events in the sale of concert tickets sold on the Twitter platform. One of the perpetrators of the fraud, as found in the tweet of the @kumiglow account. In Indonesia, the laws and regulations governing fraud both conventionally and online are contained in article 378 of the old Criminal Code (KUHP) and articles 492 to 493 of the new Criminal Code and are also contained in article 28 paragraph (1) of the ITE Law.